Koncepcje pomiaru wartości zasobów niematerialnych - Sus-Januchowska, Aleksandra (The conception of measurement value of the intangible assets, 2006)
The purpose of this article is to present the different w'ays of measurement the value of intangible assets. The individual sections of the article arc concerned with those kinds of conception which arc the most popular in an organization. The consideration presented in the article was created based on the literature studies of the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 228-236